BIJAK BERMEDIA DI ERA ARTIFICIAL INTELLIGENCE: EDUKASI HUKUM TENTANG BAHAYA DEEPFAKE BAGI PELAJAR SEKOLAH MENENGAH - M Nurkholis; Adam Nugraha; Saepul Umar; Tiara Mulsa Umami; Yarfis Dwi Nandika (PT. Hasba Edukasi Mandiri, 2026)
The development of Artificial Intelligence (AI) technology has brought about major changes in communication patterns and information distribution in the digital era, one of which is through deepfake technology, which can realistically manipulate images, sounds, and videos. This phenomenon raises legal and social issues because deepfakes can be used to spread hoaxes, defamation, fraud, and even cyber harassment. High school students are a vulnerable group due to their high level of social media use, which is not yet matched by adequate digital literacy and legal understanding. This study aims to analyze the legal status of deepfake abuse in Indonesia and the urgency of legal education for students as a preventative measure in using social media in the AI era. The study uses a normative legal method with a statutory approach and a conceptual approach through a literature review of primary, secondary, and tertiary legal materials. The results show that regulations in Indonesia, such as the ITE Law, the Criminal Code, and the Personal Data Protection Law, do not specifically regulate deepfakes, creating legal uncertainty in enforcing cases. Therefore, legal education and digital literacy are crucial for fostering awareness, media ethics, and student responsibility in responding wisely and critically to the development of AI technology.